Functional and aesthetic outcomes of alar base reduction - Abd ELAziz Ali Fahem Ali; Emad Mohammed Shehata; Hassan Mustafa Hegazy; Kamal Abd Elmonem Ebeid (The Egyptian Journal of Otolaryngology)
Abstract Background The surgical step of alar base reduction (ABR) is often done as the last stage of rhinoplasty surgery. However, it may also be done independently if the main concern is alar flare. This work was designed to assess the functional as well as aesthetic results among cases who undergo ABR which is so important to find out a better way to increase the functional, aesthetic consequences of patients. Methods This prospective study included 20 consecutive cases arranged for reduction rhinoplasty. All cases were categorized into three groups: group A (n = 6): patients with thick alar base had ABR, group B (n = 5): patients with wide nostrils had nostril size reduction, and group C (n = 9): patients with thick alar base with wide nostrils had combined alar base and nostril size reduction. Results Regarding nasal score post 1 month, levels of trouble sleeping, unable to get enough air through my nose during exercise, and total nasal obstruction symptom evaluation (NOSE) score was significantly different among all groups. Regarding nasal score post 3 month, trouble sleeping, unable to get enough air through my nose during exercise, and total NOSE score showed a significant variance among all groups (p < 0.05). Regarding standardized cosmesis and health nasal outcomes survey (SCHNOS) score post 1 month, breathing through my nose during sleep and how well my nose suits my face were significantly different among all groups (p < 0.05). Conclusions Effectiveness of ABR in improving nasal function and alleviating symptoms associated with congestion, blockage, and trouble breathing. The procedure resulted in significant improvements in various dimensions, including nasal breathing during sleep, mood, self-esteem related to the nose, and overall symmetry of the nose, as assessed by the SCHNOS score.